Maternal anxiety and previous anaphylaxis are associated with alexithymia in young patients with food allergy. Issue 1 (27th October 2021) - Polloni, Laura; Ferruzza, Emilia; Ronconi, Lucia; D'Ovidio, Giorgia; Bonaguro, Roberta; Lazzarotto, Francesca; Toniolo, Alice; Guarnaccia, Alberto; Muraro, Antonella
Abstract: Background: Alexithymia is a multifaceted personality construct described as "a lack of words to express emotions" that includes difficulty identifying feelings, difficulty describing feelings and a concrete, externally oriented cognitive style. Among patients with food allergy (FA) alexithymia has been found higher than in general population and associated with dysfunctional coping strategies. Childhood traumatic experiences and/or dysfunctional parent‐child relationship can contribute to alexithymia. The study aimed to explore possible associations between child alexithymia and mother alexithymia and anxiety, as well as previous anaphylaxis. Methods: Sixty‐five mother–child pairs have been recruited. Children had a medical diagnosis of FA. The Toronto Alexithymia Scale‐20 was used to assess alexithymia in participants. The State‐Trait Anxiety Inventory was used to assess trait anxiety in mothers. Statistical analysis was performed to investigate the influence of variables sex, previous anaphylaxis, and adrenaline auto‐injector prescription on child and mother's alexithymia and to explore possible association between maternal and child alexithymia. Results: A substantial percentage of children were alexithymic (21.5%) or borderline (33.8%), while mothers' frequencies were lower and in line with prevalence in general population. Child alexithymia was positively associated with previous anaphylaxis and mothers' trait anxiety ( p  < .05). Mother trait anxiety was also associated with maternal alexithymia. Furthermore, a positive association between child and mother alexithymia has been found. Conclusions: Clinicians must be aware of the role of alexithymia and its association with maternal anxiety and previous anaphylaxis in children with FA, encouraging seeking psychological support when needed. A multidisciplinary patient‐centered approach should be put in place for the effective care of FA.